2008
DOI: 10.1159/000205527
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Noroviruses Detected in Food Handler-Associated Outbreaks of Gastroenteritis in Japan

Abstract: Twelve outbreaks of food handler-associated gastroenteritis between November 2002 and March 2006 in Japan were examined for norovirus (NoV) using RT-PCR and sequence analysis. NoV was detected in 77 of 81 customers and 45 of 104 food handlers. Identical NoV sequences were detected in patients and food handlers in each outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…Molecular epidemiological studies of NoV strains circulating in asymptomatic food handlers found that GII.4, which has higher transmissibility than other genotypes, was dominant (17)(18)(19). However, in our study, the NoV GII-12 strain was more prevalent than GII-4.…”
contrasting
confidence: 78%
“…Molecular epidemiological studies of NoV strains circulating in asymptomatic food handlers found that GII.4, which has higher transmissibility than other genotypes, was dominant (17)(18)(19). However, in our study, the NoV GII-12 strain was more prevalent than GII-4.…”
contrasting
confidence: 78%
“…GI has been described as a genogroup that circulates to a lesser extent than GII (Castilho et al 2006, Victoria et al 2007, Barreira et al 2010. The evaluation of outbreaks that occurred in Japan during [2002][2003][2004][2005][2006] revealed that only one out of 12 outbreaks was caused by GI (Shinkawa et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…NoV has been the etiological agent of many sporadic cases and outbreaks of gastroenteritis in Japan [4,12,14,15]. Despite the limited number of positive samples used to determine seasonality, our results illustrated the great diversity of NoV strains in a limited area of Japan because GI/3, GI/4, GI/8, GII/2, GII/3, GII/4, GII/6, GII/7, GII/12, and GII/13 strains were detected.…”
Section: Figmentioning
confidence: 99%